Serving to Help and Helping to Serve: Using Servant Leadership to Influence Beyond Supervisory Relationships. (March 2022) - Kauppila, Olli-Pekka; Ehrnrooth, Mats; Mäkelä, Kristiina; Smale, Adam; Sumelius, Jennie; Vuorenmaa, Hertta
This study provides a new perspective on servant leadership research by examining the social influence of the servant leadership of individuals who are not in a supervisory position. Drawing on servant leadership and social learning theories, we examine how the servant leadership of managers in support roles can initiate a social learning process that shapes the leadership style of line managers and thereby influences employee outcomes throughout the organization. To facilitate the integration between servant leadership and social learning theories, we also examine the role of efficacy beliefs in enhancing the effectiveness of the social learning process. Using nested, time-lagged data from 667 store managers, 121 line managers, and 23 human resource managers (i.e., support managers), we find that support managers' servant leadership positively influences organizational members' perceptions of overall justice and leader-member exchange through line manager servant leadership. In turn, employees' favorable perceptions stemming from line manager servant leadership enhance the employees' organizational commitment and job satisfaction. The results also indicate that high leadership self-efficacy augments line managers' effectiveness in emulating servant leadership behaviors from support managers and reinforces the indirect effects on organizational members' favorable perceptions.